Efektivitas Pelaksanaan Program Indonesia Sehat Dengan Pendekatan Keluarga - Yohanis E.Teturan (Sekolah Tinggi Ilmu Administrasi Karya Dharma, 2024)
The Healthy Indonesia Program with a Family Approach is one way for community health centers to increase target reach and bring closer/increase access to health services in their working areas by visiting families. Various problems are believed to be the cause of the ineffective implementation of the PIS-PK program at the Kelapa Lima Community Health Center, both from the Community Health Center itself and the community. Problems in the field and health workers' statements are that the readiness of the Kelapa Lima Community Health Center in serving the PIS-PK program is still weak, limited health personnel, lack of enthusiasm from the community are one of the main problems that influence the ineffectiveness of the Kelapa Lima Community Health Center's services and the large area has an impact on services to the community. requiring. Based on data collected by health officers, the number of heads of families is 3,105. Of that number, those who receive health services in Kelapa Lima Village, only 200 heads of families receive health services by PIS-PK officers. The lack of facilities and infrastructure in the form of funds, facilities that can support the PIS-PK service activities of the Kelapa Lima Health Center. The research method used was descriptive qualitative with 17 informants. The results of the research show that the implementation of the program (PIS-PK) at the Kelapa Lima Community Health Center in Merauke has not been fully effective if we look at using five indicators. It can be seen from the Program Understanding that the majority of people do not fully understand the content of the program, as well as being on target and being on time is not fully effective from officers or the community, then there has been no significant improvement or change in achieving real goals and changes